(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
In this article, the issue of the “Durand line” is analyzed not only as a border dispute between Afghanistan and Pakistan, but also from the perspective of the clash of interests among regional and global power centers. The article also extensively discusses how the provision of regional stability is closely linked to the alignment of major powers’ strategic interests, security policies, and diplomatic approaches. Furthermore, the article provides a detailed account of the positions of the United States, China, India, the United Kingdom, and Iran regarding the “Durand line”.